Abdominal wall Type-I complex regional pain syndrome treated effectively with peripheral nerve field stimulation: a case report. Issue 1 (2nd January 2017) - Zhou, Linqiu; Chou, Henry; Holder, Eric
Abstract: Chronic abdominal wall pain is a well-documented complication of abdominal surgery. However, abdominal wall complex regional pain syndrome (CRPS) is a rare medical condition. We present a case of abdominal wall CRPS and its treatment with peripheral nerve field stimulation (PNfS). A 34-year-old female presented with right periumbilical pain for 2 years. She developed burning, sharp and stabbing pain with allodynia (extremely sensitive to wind and light touch) and erythema or pallor 2 weeks after an exploratory appendectomy. The extensive evaluation ruled out the underlining pathology. After she failed conservative therapies, she underwent a 7-day trial of thoracic spinal cord stimulation (SCS) and abdominal wall PNfS. Thoracic SCS failed to provide pain relief; however, PNfS provided significant relief (>90%) of burning sensation. It has now been 5 years since the PNfS was implanted and she continues to demonstrate substantial pain relief.